Early oxidation stages of germanium substrate in the graphene/Ge(001) system. (August 2019) - Dabrowski, P.; Rogala, M.; Pasternak, I.; Krukowski, P.; Baranowski, J.M.; Strupinski, W.; Lutsyk, I.; Kowalczyk, D.A.; Pawłowski, S.; Klusek, Z.
Abstract: Kelvin Probe Force Microscopy (KPFM) in combination with Atomic Force Microscopy (AFM), Scanning Tunneling Microscopy/Spectroscopy (STM/STS), and X-ray Photoelectron Spectroscopy (XPS) were used to study early stages of oxidation of germanium in the graphene/Ge(001) system exposed to atmospheric environment. KPFM measurements allowed to distinguish nanoscale regions, which are not covered by graphene, as a result of graphene domain misorientation in the growth process. In this area, corrosion process penetrated the region underneath graphene, which can be observed at the nano- and microscale. Therefore, the electronic properties of graphene/germanium hybrid system are modified in the regions around defects. Whereas graphene can protect surfaces against oxidation, the described processes have impact of electronic properties of the sample in a long time scale. We showed that early oxidation stages can be identified in nanoscale even when macroscopic techniques such as XPS do not show signs of degradation. The obtained results are important for assessing the need of protection of graphene/Ge(001) devices. Graphical abstract: Image 1